PENENTUAN RUTE TERBAIK PADA DISTRIBUSI PRODUK X DI PT BCD MENGGUNAKAN METODE SAVING MATRIX DAN NEAREST NEIGHBORS - Faghan Jihad Azhar; Alifah Nur Astari; Crisna Amar Rizky; Muchammad Fauzi (LPPM Universitas Bina Bangsa, 2023)
PT BCD is a company engaged in the distribution of drugs, pharmaceuticals and other consumer goods. PT BCD distributes products supplied by factories to consumers in the form of outlets, pharmacies and other large pharmaceutical companies (PBF), one of them is x product. To deliver x product to customers, PT BCD uses transportation in the form of box cars. In 2023, the Head of Expedition at PT BCD wants to determine which route should be taken so that the shipping process can be carried out effectively and efficiently and also can provide benefits in the form of savings. Therefore, this research was conducted to study the best route that should be taken by the expedition team using the Saving Matrix and Nearest Neighbors methods. Based on the results of data processing and analysis carried out using both methods, the best route was obtained which was able to provide savings of 39.61% with a total distance reduction of 46.1 km